2013
DOI: 10.1111/1462-2920.12242
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and structural response of heterotrophic bacteria to dissolved organic matter of different chemical composition in a continuous culture study

Abstract: Dissolved organic matter (DOM) and heterotrophic bacteria are highly diverse components of the ocean system, and their interactions are key in regulating the biogeochemical cycles of major elements. How chemical and phylogenetic diversity are linked remains largely unexplored to date. To investigate interactions between bacterial diversity and DOM, we followed the response of natural bacterial communities to two sources of phytoplankton-derived DOM over six bacterial generation times in continuous cultures. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 74 publications
(92 reference statements)
17
95
0
Order By: Relevance
“…This number is similar to the percentage of molecular formulae attributed to phytoplankton and/or biodegradation-related processes in the Amazon (Medeiros et al, 2015b). The authors report selective removal of compounds with high O/C ratios via biodegradation (Sun et al, 1997;Kim et al, 2006) and input of phytoplankton-derived material of low O/C ratio (Landa et al, 2014). This was not observed for the Delaware system, where we found that oxygen-rich polyphenols and highly unsaturated compounds increased with chlorophyll a concentration.…”
Section: Seasonal Dom Imprint Due To Biological Processessupporting
confidence: 85%
“…This number is similar to the percentage of molecular formulae attributed to phytoplankton and/or biodegradation-related processes in the Amazon (Medeiros et al, 2015b). The authors report selective removal of compounds with high O/C ratios via biodegradation (Sun et al, 1997;Kim et al, 2006) and input of phytoplankton-derived material of low O/C ratio (Landa et al, 2014). This was not observed for the Delaware system, where we found that oxygen-rich polyphenols and highly unsaturated compounds increased with chlorophyll a concentration.…”
Section: Seasonal Dom Imprint Due To Biological Processessupporting
confidence: 85%
“…High PP allows taxa to react to changing environmental conditions. Consequently, our results may in part explain why the composition of the bacterial communities was not different between treatments in Exp_CyDi (Landa et al 2013b). The continuous cultures possibly selected for versatile taxa that are adapted to a variety of available carbon sources, and indeed the microbial taxa dominating the continuous culture communities, have been identified in previous studies as opportunists that grow well in laboratory situations (Supplementary Table S2).…”
Section: Discussionsupporting
confidence: 52%
“…In Exp_CyDi, bacterial abundances remained stable at 4.2-5.1 Â 10 6 cells per ml until day 8, after which a decrease in bacterial abundances was detectable until day 11, followed by a second stable phase at 5.2-7.5 Â 10 5 cells per ml. This decrease in bacterial abundance was accompanied by an increase in heterotrophic nanoflagellates (Landa et al, 2013b). Metatranscriptomic analyses were performed on samples collected for both experiments at day 15.…”
Section: Microbial Dynamics In the Continuous Culturesmentioning
confidence: 99%
“…Still, recent advances provided a new look at an old topic: our understanding of DOC-bacteria interaction has moved from an extreme specialization view, where few specific bacterioplankton strains responded to a particular phytoplankton species (for example, González et al, 2000;Schafer et al, 2002;Pinhassi et al, 2004;Grossart et al, 2005;Rooney-Varga et al, 2005;Sapp et al, 2007a) to a more moderate (generalist) and complex view where many types of bacteria are involved in the decomposition of different types of DOCp with differences in their uptake rates (Nelson and Carlson, 2012;Sarmento and Gasol, 2012;Landa et al, 2013;Paver et al, 2013;Morana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%